The Impact of Audit Quality, Attributes of The Audit Committee, and Institutional Ownership on the Promptness of Financial Reporting - Rajagukguk, Thetty Surienty (Accounting Studies and Tax Journal (COUNT), 2024)
This research investigates and tries to find empirical evidence regarding the impact of audit quality, audit committee characteristics, and institutional ownership on the timeliness of submitting financial reports. The method’s approach applied in this research is associative quantitative research using secondary data in the form of annual financial reports taken from the official website of the Indonesia Stock Exchange. All Food and Beverage sector companies listed on the Indonesian Stock Exchange are the population for this research. The sample was selected by applying a purposive sampling technique using predetermined criteria. The total number of samples used was 60 data over a research period of 5 years. The analytical method applied in this research is multiple linear analysis using the Eviews 9 program. The findings of this research show that there is an impact of auditor quality on the timeliness of submitting financial reports, while the size of the audit committee, frequency of audit committee meetings, and institutional ownership do not have a significant influence on the timeliness of submitting financial reports.